Criminal Policy of Adultery in Indonesia - Widyawati, Anis (Universitas Negeri Semarang, 2020)
Judge courage needed in deciding adultery cases in article 284 of the Criminal Code for perpetrators who have not been bound by marriage, the judge can apply based on the 1945 Constitution and the Law on Judicial Power, which states the source of law is not only the Law (expansion of the principle of material legality) but can also source from code that lives in the community (customary law). This research is intended to analyze and describe the penal policy (criminal law policy and politics of criminal law) concerning adultery in Indonesia. This research uses normative legal research, where the Author analyze and compare all laws and regulations concerning to adultery in Indonesia and some theories of adultery in global context. This paper emphasized that adultery not only against religious values but also customary values (customary law). The formulation of adultery concept in Indonesian Penal Code affected by religious teachings and national ideology of Pancasila.